The ontogenetic origins of skull shape disparity in the Triturus cristatus group. Issue 5 (14th August 2014) - Cvijanović, Milena; Ivanović, Ana; Kalezić, Miloš L.; Zelditch, Miriam L.
SUMMARY Comparative studies of ontogenies of closely related species provide insights into the mechanisms responsible for morphological diversification. Using geometric morphometrics, we investigated the ontogenetic dynamics of postlarval skull shape and disparity in three closely related crested newt species. The skull shapes of juveniles just after metamorphosis (hereafter metamorphs) and adult individuals were sampled by landmark configurations that describe the shape of the dorsal and ventral side of the newt skull, and analyzed separately. The three species differ in skull size and shape in metamorphs and adults. The ontogenies of dorsal and ventral skull differ in the orientation but not lengths of the ontogenetic trajectories. The disparity of dorsal skull shape increases over ontogeny, but that of ventral skull shape does not. Thus, modifications of ontogenetic trajectories can, but need not, increase the disparity of shape. In species with biphasic life‐cycles, when ontogenetic trajectories for one stage can be decoupled from those of another, increases and decreases in disparity are feasible, but our results show that they need not occur.